IFRS S2: perspectives of respondents from BRICS regarding the climate-related disclosure standard - Sato, Pedro Henrique Godoy; Bonfim, Mariana Pereira (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Purpose: To analyze the opinion of participants in comment letters from BRICS countries (Brazil, Russia, India, China, and South Africa) on the draft IFRS S2 - Climate-related Disclosures, issued by the International Sustainability Standards Board (ISSB). Methodology: The 700 letters sent globally, and subsequently, the 43 letters sent by the countries that make up BRICS, were analyzed using ChatPDF and ATLAS.ti software. Results: The analysis showed that most letters range from 1 to 10 pages, with 92% of the correspondence sent by organizations, mainly from agencies, alliances, and associations. Geographically, countries such as the United Kingdom, the United States, Canada, Australia, France, Japan, Germany, and Switzerland stood out. In the context of BRICS, South Africa and Brazil's participation was notable, while Russia did not send any letters. A detailed analysis of the BRICS letters revealed that responses emphasized the importance of precise terminology, the use of both qualitative and quantitative approaches in disclosures, and the inclusion of transition plans and decarbonization targets. The main challenges identified were implementation difficulties in emerging economies and high costs, suggesting a phased and flexible approach. Recommendations include adopting the concept of double materiality, creating a universal glossary, and standardizing digital documents. Responses showed strong support for the objectives of the draft IFRS S2, underscoring the need for strong, inclusive climate governance. Contributions of the Study: This work enhances the understanding of stakeholder perceptions and how organizations in BRICS countries align with international standards. The data aims to support various actors within the IFRS S2 framework: i) the ISSB itself, by understanding the views of key countries in the global economy, such as the BRICS, to help them develop new regulations; ii) governments, in shaping their public policies based on stakeholder perspectives; iii) society, by highlighting the demands from standard-setting bodies and companies regarding sustainability.